Racanalization in Acute Ischemic Stroke (Ictus, 2020)
Clinical snapshot of a case of cerebral reperfusion in a patient who did not know the time of onset of symptoms.
Keywords: Ischemic Stroke; Reperfusion; Thrombectomy